Semidominant mutations in the yeast Rad51 protein and their relationships with the Srs2 helicase. - Chanet, R (1996)
Suppressors of the methyl methanesulfonate sensitivity of Saccharomyces cerevisiae diploids lacking the Srs2 helicase turned out to contain semidominant mutations in Rad5l, a homolog of the bacterial RecA protein. The nature of these mutations was determined by direct sequencing. The 26 mutations characterized were single base substitutions leading to amino acid replacements at 18 different sites. The great majority of these sites (75%) are conserved in the family of RecA-like proteins, and 10 of them affect sites corresponding to amino acids in RecA that are probably directly involved in ATP reactions, binding, and/or hydrolysis. Six mutations are in domains thought to be involved in interaction between monomers; they may also affect ATP reactions. By themselves, all the alleles confer a rad5l null phenotype. When heterozygous, however, they are, to varying degrees, negative semidominant for radiation sensitivity; presumably the mutant proteins are coassembled with wild-type Rad51 and poison the resulting nucleofilaments or recombination complexes. This negative effect is partially suppressed by an SRS2 deletion, which supports the hypothesis that Srs2 reverses recombination structures that contain either mutated proteins or numerous DNA lesions.